Event-based multirate control of large-scale distributed nonlinear systems subject to time-driven zero order holds. (May 2020) - Zhong, Zhixiong; Zhu, Yanzheng; Basin, Michael V.; Lam, Hak-Keung
Abstract: The event-based output-feedback control is studied for large-scale distributed networked nonlinear systems. All subsystems are described by interval type-2 (IT2) Takagi–Sugeno (T–S) model and communicate information to each other via distributed networks with time-varying transmission delays. The sampled rates of sensors and refresh rates of actuators are allowed to be different among subsystems. We propose an event-based control scheme in the sense that each subsystem determines its information transmission to other subsystems based on its local sampled output measurements. First, combined with the descriptor system and perturbed system approaches, an equivalent model transformation is established. Then, a relaxing Lyapunov functional is introduced by virtue of Wirtinger inequality. The corresponding co-design criteria are obtained in the form of linear matrix inequalities (LMIs), which guarantee stabilization of the closed-loop fuzzy control system with different sampling and updating rates while transmitting information via networks as little as possible. Furthermore, employing some bounding inequality techniques, a considerable reduction in the number of LMIs can be achieved. Finally, a practical application to a DC microgrid with three PV subsystems is exploited.